Analysis of the Influence of Organizational Learning, Employer Branding and Work Flexibility on Workplace Innovation Behavior of Creative Industry Workers - Lenny Nuraeni; Rasty Yulia; Ali Zaenal Abidin; Sardin; Cindy Sandra Lumingkewas; Fatimah Malini Lubis (Journal of Innovative and Creativity, 2025)
The purpose of this research examine how organizational learning, employer branding, and flexibility of work determine employee innovative behavior in the creative industry sector. In this study, quantitative method using survey design was employed, specifically with a sample size of 120 purposively selected respondents. A five-point Likert scale questionnaire was used in the data collection process. Before performing a multiple linear regression analysis, the data was subjected to classical assumption tests of normality, heteroscedasticity, and multicollinearity. The analysis findings indicate that all three variables, organizational learning, employer branding, and work flexibility, jointly impacted innovative behavior at work, evidenced by an R² value of 0.68. Partially, each variable also showed a positive effect, indicating that the stronger the learning culture in the organization, the more positive the perception of employer branding, and the greater the work flexibility provided, the higher the level of innovation demonstrated by employees. This study contributes to the development of theory in the field of human resource management and can serve as a basis for creative companies in developing strategies to create a work environment that encourages sustainable innovation.